Mommyblogs and the Changing Face of Motherhood - Friedman, May, 1975- (Book collections on Project MUSE., 2013)
Mothers have consistently relied upon one another for guidance and support as they navigate the difficult world of parenting. For many women, the increasingly established online community of "mommyblogs" now provides a source of camaraderie and support that acknowledges both the work of mothering and the implications of its undertaking. Beyond their capacity to entertain, how have mommyblogs shifted our understanding of twenty-first-century motherhood? In examining the content of hundreds of mommyblogs, May Friedman considers the ways that online maternal life writing provides a front row seat to some of the most raw, offbeat, and engaging portraits of motherhood imaginable. Focusing on the composition of the "mamasphere" and on mommyblogs' emphasis on connection, Friedman reveals the changing face of contemporary motherhood - one less concerned with the proscriptions of what good mothers should do, and more invested in what diverse mothers have to say.